(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To assess cytological conjunctival changes in patients with type 2 diabetes mellitus (T2DM)-associated dry eye disease in the presence of treatment with a combination of trehalose and sodium hyaluronate. Material and Methods: This study was conducted at the Pirogov Vinnytsia Regional Clinical Hospital, the clinical site of the National Pirogov Memorial Medical University, from April to December 2023. We used prospective data of 46 patients (92 eyes; mean age, 62.47 ± 6.24 years). Results: Most patients (67%) showed abnormal conjunctival impression cytology (CIC) changes (Nelson’s grade 2 and 3) before treatment. Among these, grade 3 squamous metaplasia was twice as common as grade 2 squamous metaplasia; this demonstrated apparent CIC changes in the group of patients, and a substantial prevalence of squamous metaplasia in type 2 diabetics. After treatment with a combination of trehalose 3% plus sodium hyaluronate 0.15%, neutrophil infiltration was observed only in 5 (11%) patients (р = 0.0375), which may indicate an anti-inflammatory effect of the combination. Conclusion: We found a significant effect of a combination of trehalose 3% plus sodium hyaluronate 0.15% on the state of the ocular surface, with the resolution of inflammatory conjunctival infiltration, in patients with T2DM (p = 0.0375). Because stabilization or slowing of damage to epithelial cells is important for patients with T2DM and was observed in the presence of treatment with the combination eye drop, these patients require long-term treatment with the medication.